223k views
4 votes
Instructions: Fill in the last step of solving the quadratic equation by factoring. 3x2−2x−5=0 Step 1: Rewrite middle term. 3x2−5x+3x−5=0 Step 2: Group terms together and find GCF. (3x2−5x)+(3x−5)=0 x(3x−5)+1(3x−5)=0 (3x−5)(x+1)=0 Step 3: Apply the Zero Product Property. 3x−5=0 or x+1=0 Step 4: Solve. x= or x=

1 Answer

5 votes

Answer:

x = (5/3)

x = -1

Explanation:


3x^2 -2x - 5 =0\\\\(3x^2+3x) + (-5x - 5) = 0\\\\(3x-5)(x+1)=0\\\\\left \{ {{3x-5=0} \atop {x+1=0}} \right.\\\\===========\\\\3x - 5 = 0\\\\3x - 5 + 5 = 0 + 5\\\\3x = 5\\\\(3x=5)/(3)\\\\x = (5)/(3)\\\\===========\\\\x + 1 = 0\\\\x + 1 - 1 = 0 - 1\\\\x = -1 \\\\===========\\\\\boxed{\text{Therefore:}}\\\\\boxed{ x = (5)/(3) \text { or } x = -1}

You would just need to solve the two equations from step three for 'x'.

Hope this helps you.

User Parth Chavda
by
5.1k points